Impact of lymphovascular space invasion on a nomogram for predicting lymph node metastasis in endometrial cancer - Koskas, Martin; Bassot, Karine; Graesslin, Olivier; Aristizabal, Patrick; Barranger, Emmanuel; Clavel-Chapelon, Françoise; Haddad, Bassam; Luton, Dominique; Darai, Emile; Rouzier, Roman (Gynecologic oncology, 2013)
The aim of this study was to evaluate the impact of lymphovascular space invasion (LVSI) on nomogram-based predictions of lymph node (LN) metastasis in endometrial cancer. The data from 485 patients with presumed stage I or II endometrial cancer who underwent hysterectomy and lymphadenectomy were analyzed. Calibration curves were designed and compared for three different subgroups: LVSI-positive tumors (n=113), LVSI-negative tumors (n=213) and LVSI-undetermined tumors (n=159). In the entire population, the nomogram showed good discrimination with an area under the receiver operating characteristic curve (AUC) of 0.80 and was well calibrated. In the subgroup analyses, in LVSI-positive, LVSI-negative and LVSI-undetermined patients, the nomogram was not well calibrated (p of the U index of 0.028, 0.087 and 0.011, respectively) with underestimation in LVSI-positive patients and overestimation in LVSI-negative and LVSI-undetermined patients of LN metastasis. In the univariate analysis and after adjusting for the LN metastasis probability provided by the nomogram, LVSI-positive tumors were associated with an increased risk for LN metastasis compared with LVSI-negative tumors (RR=7.29 [3.87–13.7] and 5.04 [2.30–11.08], respectively). In contrast, the univariate analysis and after adjusting for the LN metastasis probability provided by the nomogram showed that LVSI-undetermined tumors were not associated with an increased risk for LN metastasis compared with LVSI-negative tumors (RR=0.73 [0.32–1.69] and 1.26 [0.47–3.37], respectively). Our results suggested that LVSI should be considered to be an independent risk factor for LN metastasis. In this multicenter study, the risk for LN metastasis is similar when the LVSI is negative or is not detailed in the pathological report. ► We evaluated the impact of lymphovascular space invasion on nomogram-based predictions of lymph node metastasis in endometrial cancer. ► The nomogram showed underestimation in LVSI-positive patients and overestimation in LVSI-negative and LVSI-undetermined patients for predicting lymph node metastasis. ► In this multicenter study, the risk for LN metastasis was similar when the LVSI is negative or is not detailed.